Engaging industry in curriculum design and delivery in public policy teaching: A strategic framework. Issue 1 (March 2020) - Manwaring, Rob; Holloway, Josh; Coffey, Brian
Public policy is frequently characterised as a sub-discipline of political science which is practically oriented and concerned with what government does and does not do. Further, policy analysis can also be characterised as concerned with either the analysis 'of policy' or 'for policy'. This clearly has implications for the design and delivery of public policy courses. More broadly, higher education in Australia, like elsewhere, faces calls to ensure that students graduate with a range of skills and aptitudes that make them 'job ready' and able to engage with 'real world problems'. One of the ways in which this can be pursued is through industry engagement. However, limited research has been undertaken regarding what this might entail or how it can be pursued. Accordingly, in this paper we explore these issues by: (a) situating engagement within the field of public policy; (b) reviewing how the changing context of higher education, with a particular focus on the drivers and rationale for greater engagement with industry, intersects with the teaching of public policy; and (c) providing a framework which helps to clarify the different modes, potential and risks associated with industry engagement.